JAXA protein crystallization in space: ongoing improvements for growing high‐quality crystals. (25th September 2013) - Takahashi, Sachiko; Ohta, Kazunori; Furubayashi, Naoki; Yan, Bin; Koga, Misako; Wada, Yoshio; Yamada, Mitsugu; Inaka, Koji; Tanaka, Hiroaki; Miyoshi, Hiroshi; Kobayashi, Tomoyuki; Kamigaichi, Shigeki
<x xml:space="preserve">Abstract</x> The Japan Aerospace Exploration Agency (JAXA) started a high‐quality protein crystal growth project, now called JAXA PCG, on the International Space Station (ISS) in 2002. Using the counter‐diffusion technique, 14 sessions of experiments have been performed as of 2012 with 580 proteins crystallized in total. Over the course of these experiments, a user‐friendly interface framework for high accessibility has been constructed and crystallization techniques improved; devices to maximize the use of the microgravity environment have been designed, resulting in some high‐resolution crystal growth. If crystallization conditions were carefully fixed in ground‐based experiments, high‐quality protein crystals grew in microgravity in many experiments on the ISS, especially when a highly homogeneous protein sample and a viscous crystallization solution were employed. In this article, the current status of JAXA PCG is discussed, and a rational approach to high‐quality protein crystal growth in microgravity based on numerical analyses is explained.